PANDEMIC OF THE TWENTY-FIRST CENTURY: : WORLD-CLASS SOCIO-ECONOMIC CRISIS - Petrovich Garnov, Andrey; Alekseevna Prodanova, Natalia; Yuryevna Garnova, Victoria; Yurievna Kamchatova, Ekaterina; Ivanovna Zatsarinnaya, Elena (Revista Gênero e Interdisciplinaridade, 2020)
The second half of the twentieth century - the era of the scientific and technological revolution, which brought a powerful rise in technocratic and scientist ideas, followed by the development of concepts of the information society, industrial society and post-industrial society. These concepts are specified in the theories of a consumption society, a leisure society, a technotron, technocratic and computerized society. The aim of the study is to consider the concept of technological determinism, which is considered panacea for all social diseases. The article reveals the main reason for the global crisis 2020. The study also determines that scientific and technological progress creates objective grounds for social progress, but, unfortunately, is not able to solve global problems at present. From the author’s point of view, these problems themselves are determined not so much by the development of science and technology as by the form of ownership of the means of production. The era of scientific and technological revolution that